Pilot study of a 3-day residential treatment for smoking cessation in Hong Kong - HO, Raymond Kin Sang (Tob Prev Cessat, 2018)
INTRODUCTION: The Tung Wah Group of Hospitals Integrated Centre on Smoking Cessation has been providing free smoking cessation services since 2009. The average quit rate from 2009 to 2014 was 37%. In order to boost the quite rate, we have implemented a residential treatment program for smokers who volunteered to participate. Having run the program for two years, we conducted a retrospective cohort study to evaluate its effectiveness. METHODS: We recruited the participants who had failed previous quit attempts and who came to seek our smoking cessation services. A 3-day residential program of activities were arranged for our participants. Intensive individual and group counseling was provided. Pharmacotherapy was also provided to alleviate withdrawal symptoms. This was followed by our usual treatment and follow-up program. Self-reported 7-day point prevalence abstinence rate at 26 weeks based on intention-to-treat (ITT) analysis was assessed. RESULTS: A total of 40 clients volunteered to join the program, age 26 to 65 years old with a mean of 44.1 years. There were 25 (62.5%) males and 15 (37.5%) females. The quit rate at 26 weeks was 57.5%. Smokers older than 43 years, having cohabiting smokers, and smoking for more than 28 years, were more likely to quit and this was statistically significant. CONCLUSIONS: This pilot study demonstrated that a 3-day residential program is effective in helping addicted smokers who volunteer to quit smoking and is cost effective compared to longer residential programs.